ChemInform Abstract: Five‐Membered Heteroaromatic Ring Fused‐Pyrimidine Derivatives: Design, Synthesis, and Hedgehog Signaling Pathway Inhibition Study. Issue 5 (February 2015) - Zhang, Liandi; Xin, Minhang; Shen, Han; Wen, Jun; Tang, Feng; Tu, Chongxing; Zhao, Xinge; Wei, Ping
Abstract Among the new pyrimidine derivatives, compounds (I) are the most potent hedgehog signaling pathway inhibitors.